Child Marriage: Concept Paper - Shumba, Precious; Mary Kasu, Christine; Mugadza, Gladys (IJRDO - Journal of Social Science and Humanities Research, 2017)
Marriage or being in union before the age of 18 years is still a reality for many girls and a few boys all over the world. The objective of this paper was therefore to clarify, explain and define the concept child marriage in a bid to initiate standardization of child laws within countries and prevent breaching of the value of a child in order to curb child marriage. Walker and Avant’s (2005) strategic method of concept analysis was used to analyze the concept of interest. Researchers conducted literature search in one month using Google Scholar, Pub-med and MEDLINE as search engines and fifteen studies were reviewed. Conflicting definitions of a child, marriage customs and fragmented legal framework within countries led to perpetuation of this harmful marriage practice. Eradication of child marriage protects the child’s rights and empowerment for a better society.